A health belief model-based community health education on mammography screening among reproductive-aged women in Ethiopia: a randomized controlled trial - Agide, Feleke Doyore; Garmaroudi, Gholamreza; Sadeghi, Roya; Shakibazadeh, Elham; Yaseri, Mehdi; Koricha, Zewdie Birhanu (Frontiers in Public Health, 2024)
Background Early intervention in mammography use prevents breast cancer-related deaths. Therefore, this study aimed to apply health education interventions to mammography use in reproductive-aged women. Methods This was a sequential exploratory design using qualitative and quantitative methods. The qualitative part used to gain insights into the design and development of interventions. For the randomized trial, a sample of 405 participants was recruited in each arm. The mean difference of interventions on the study variables was determined using a general linear model for repeated measures (ANOVA). For dichotomous variables, nonparametric tests (Cochran Q) were used. Path analysis was used to observe how the constructs of the Health Belief Model interacted. We registered PACTR database (https://pactr.samrc.ac.za/): “PACTR201802002902886.” Results The study found that there was a strong interplay between perceptions of mammography screening and the intervention, showing that the likelihood of mammography use and comprehensive knowledge increased from baseline to endpoint (p < 0.005). Likewise, health motivation and all constructs of the health belief model had a statistically significant mean difference between the intervention and control groups (p < 0.005). However, the mean value of perceived barriers in the intervention group was statistically significantly reduced after three and six months (mean difference = −2.054 between Measure 1 and measure 2 and −1.942 between Measure 2 and Measure 3). The hypothesized causal paths effect of the model was explained by 64.3% that shows there is strong relationship of the variables significantly (p < 0.005). Conclusion The study found that model-based mammography screening interventions had a significant impact at various time periods. We recommend future researchers consider the intensity and range of information to advance the field and figure out the problem while investigating the dose and peak of the intervention.